Effect of Grinding Wheel Loading on Force and Vibration - Anbazhagan , R.; Mohankumar, D. (International Journal of Psychosocial Rehabilitation, 2018)
: Grinding wheels are applied in industry in a large variety of ways such as centre less, cylindrical, external and internal, surface and double disc etc. under a variety of cutting conditions. The abrasive grinding wheels has two major roles. The first role is inherent in which the wheel rotates to its function with regard to the production of good surface finish and the ease of material removal in grinding. The second role refers to the apparent behavior of the grinding wheel and depends upon the interaction of the wheel with the characteristics of the grinding machine and other application conditions. A grinding wheel is a very forgiving tool and its grinding action is somewhat dynamic in that it can be altered significantly by changing the grinding conditions.